Gagal Jantung akibat Kardiomiopati Alkoholik pada Pria Muda: Laporan Kasus - Darmawan, Rizky (Cermin Dunia Kedokteran, 2025)
Background: Alcoholic cardiomyopathy (ACM) is cardiomyopathy caused by consuming large amounts of alcohol. Diagnosis is determined based on alcohol consumption’s history, clinical, and supporting data. Case: Male, 29 years old, came with shortness of breath especially when walking, lying down, and waking-up at night. The patient has been consuming 4 bottles of “Flores wine”/day for the past 14 years. Physical examination showed BP 124/93, pulse 101 x/min, RR 24 x/min, left apex and parasternal area systolic murmur, basal rhonchi, and edema of both feet. Electrocardiography showed RAD, RAE, LBBB, and LVH. Chest x-ray showed cardiomegaly and minimal pleural effusion. Laboratory examination showed SGOT 986.2 U/L, SGPT 448.3 U/L, and electrolyte imbalance. TTE results showed global hypokinetics, all cardiac chambers dilatation, reduced LV systolic function (EF 21.6%), severe TR, and moderate-severe MR. Angiography results showed no stenosis in all coronary arteries. MRI result is similar to TTE without late gadolinium enhancement (LGE). Therapy given according to guided-directed medical therapies (GDMT). Conclusion: ACM is cardiomyopathy with highly variable objective findings. In-depth history regarding alcohol consumption is crucial and other possible causes must be excluded.